Non-tuberculous mycobacteria in patients with bronchiectasis. Issue 12 (14th October 2005) - Wickremasinghe, M; Ozerovitch, L J; Davies, G; Wodehouse, T; Chadwick, M V; Abdallah, S; Shah, P; Wilson, R
Abstract : Background: Non-tuberculous mycobacteria (NTM) are ubiquitous environmental organisms. Patients with pre-existing lung damage are susceptible to NTM, but their prevalence in bronchiectasis is unknown. Distinguishing between lung colonisation and disease can be difficult. Methods: A prospective study of 100 patients with bronchiectasis was undertaken to evaluate the prevalence of NTM in sputum, and a retrospective analysis of clinical, microbiological, lung function and radiology data of our clinic patients with NTM sputum isolates over 11 years was performed. Results: The prevalence of NTM in this population of patients with bronchiectasis was 2%. Patients in the retrospective study were divided into three groups: bronchiectasis + multiple NTM isolates (n = 25), bronchiectasis + single isolates (n = 23), and non-bronchiectasis + multiple isolates (n = 22). Mycobacterium avium complex (MAC) species predominated in patients with bronchiectasis compared with non-bronchiectasis lung disease (72% v 9%, p<0.0001). Single isolates were also frequently MAC (45.5%). Multiple isolates in bronchiectasis were more often smear positive on first sample than single isolates (p<0.0001). NTM were identified on routine screening samples or because of suggestive radiology. No particular bronchiectasis aetiology was associated with an NTM. Pseudomonas aeruginosa and Staphylococcus aureus were frequently co-cultured. Six (25%) of multiple NTM patients had cavities of which five were due to MAC. Half the patients with multiple isolates were treated, mostly due to progressive radiology. Conclusions: NTM are uncommon in non-cystic fibrosis bronchiectasis. Routine screening identifies otherwise unsuspected patients. MAC is the most frequent NTM isolated.